'Creative histories' and the Australian context. Issue 2 (3rd April 2022) - Lindsey, Kiera; Smith, Mariko; Clark, Anna; Batty, Craig; Brien, Donna; Landers, Rachel
Abstract: This article brings together a group of history practitioners who, prompted by their experiences of creative approaches to the theory and practice of history, are exploring how the term 'Creative Histories' might apply within the Australian context. While the term and practice of Creative Histories has gained international currency in recent years, little has been done to consider its development and relevance in Australia. Here we develop a working definition for the term which has been shaped in conversation with Creative Historians at the University of Bristol and a suite of interviews conducted with 10 Australian 'creative historians' who have worked or still work within the academy, as well as four Indigenous artists, academics and activists who each employ creativity in the ways they 'practice the past'. Together, these influences indicate that questions of purpose, poetics and politics go to the heart of Creative Histories in Australia and that a fuller understanding of both Creative Histories and the creative histories of Aboriginal practitioners will make a useful contribution to conversations concerned with decolonising the discipline in Australia.